A school-based behaviour change intervention to increase physical activity levels among Chinese children: intervention development and cluster non-randomised controlled feasibility trial - Wang, Haiquan (2022)
Children in China have low levels of physical activity. The aim of this thesis was to develop a school-based behaviour change intervention to increase physical activity levels among Chinese children and to determine the feasibility of undertaking the definitive cluster randomised controlled trial (RCT) in China. In order to achieve this aim, four inter-related studies were conducted: